Culture wars: secular-catholic conflict in nineteenth-century Europe - Clark, Christopher M.; Kaiser, Wolfram (Cambridge University Press, 2003)
Across nineteenth-century Europe, the emergence of constitutional and democratic nation-states was accompanied by intense conflict between Catholics and anticlerical forces. At its peak, this conflict touched virtually every sphere of social life: schools, universities, the press, marriage and gender relations, burial rites, associational culture, the control of public space, folk memory and the symbols of nationhood. In short, these conflicts were 'culture wars', in which the values and collective practices of modern life were at stake. These 'culture wars' have generally been seen as a chapter in the history of specific nation-states. Yet it has recently become increasingly clear that the Europe of the mid- and later nineteenth century should also be seen as a common politico-cultural space. This book breaks with the conventional approach by setting developments in specific states within an all-European and comparative context, offering a fresh and revealing perspective on one of modernity's formative conflicts.